Effects of renal sympathetic denervation on cardiac systolic function after myocardial infarction in rats - Guo, Jiqun (J Biomed Res, 2016)
This study investigated the therapeutic effects of renal denervation on cardiac systolic function after myocardial infarction (MI) in rats and the mechanism involved. Fifty male SD rats were randomly assigned to the sham group (n = 15), the MI group (n = 20), and the MI plus renal denervation group (n = 15). MI was established through thoracotomic ligation of the anterior descending artery. Renal denervation was achieved by laparotomic stripping of the renal arterial adventitial sympathetic nerve, approximately 3 mm from the abdominal aorta. Left ventricular function and hemodynamics were measured several weeks following MI. The left ventricular systolic function of the MI group was significantly reduced and the systolic blood pressure (SBP) remarkably declined. In rats with MI treated with renal denervation, the left ventricular ejection fraction (EF), fractional shortening (FS) and SBP markedly improved compared with the MI group. However, heart rate and fibrosis decreased significantly. These findings suggest that renal denervation has therapeutic effects on post-MI cardiac dysfunction. These effects are associated with increased left ventricular ejection fraction (LVEF) and SBP, as well as reduced heart rate and fibrosis. This may represent a new approach to the treatment of post-MI remodeling and subsequent heart failure.